The Influence of Sustainability, Governance, and Financial Performance on Investment - Eka Santi Agustina (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Growing investor interest in sustainable practices has pushed Indonesian private firms in the industrial gas sector to integrate environmental, social, and governance factors, corporate governance, and financial performance to attract capital. This study aims to examine how these factors influence investment decisions, using a quantitative approach with multiple linear regression analysis. Data were collected from quarterly financial reports, sustainability documentation, and investment records of private firms from February to April 2025, totaling 45 observations. The findings show that financial performance, measured by profitability ratios, has the strongest impact on investment, followed by corporate governance through transparent reporting and board oversight, and environmental, social, and governance factors, all significantly affecting investment both individually and collectively. The model explains 91% of investment variation, highlighting its robustness. However, reliance on internal sustainability metrics limits comparability. Firms must balance strong financial results with governance and sustainability efforts to boost investor confidence, though standardizing metrics remains a challenge for private firms.